Association of exposure to ambient air pollution with ovarian reserve among women in Shanxi province of north China. (1st June 2021) - Feng, Xiaoqin; Luo, Jinhong; Wang, Xiaocheng; Xie, Wolong; Jiao, Jiao; Wu, Xiaohui; Fan, Lingling; Qin, Guohua
Abstract: Air pollution has been an important risk factor for female reproductive health. However, epidemiological evidence of ambient air pollution on the predictor for ovarian reserve (antral follicle count, AFC) is deficient. We aim to comprehensively evaluate the association of long-term exposure to ambient air pollution with AFC among women of reproductive age in Shanxi of north China. 600 women with spontaneous menstrual cycle, not using controlled ovarian stimulation, were enrolled in the retrospective study. Two distinct periods of antral follicle development were designed as exposure windows. Generalized linear model was employed to estimate the change of AFC associated with exposure of atmospheric pollutants (SO2, NO2, PM10, PM2.5, CO and O3 ). Stratification analysis based on age (<30, ≥30 years), university degree (yes, no), years of exposure (2013–2016, 2017–2019) and duration of infertility (<2, 2–5, >5 years) along with two pollutants model were employed to further illustrate the association. We found every 10 μg/m 3 increase in SO2 concentration level during the entire development stage of antral follicle was associated with a −0.01 change in AFC (95% confidence interval: −0.016,  −0.002) adjusting for the confounders including age, BMI, parity and infertility diagnosis factors. The significant association of increased SO2 level with decreased AFC was particularly observed during the early transition from primary follicle to preantral follicle stage by 10 μg/m 3 increase in SO2 exposure level with a −0.01 change (95% CI: -0.015,  −0.002) in AFC. The negative association was pronounced among women aged ≥30 years old, and also significant in two pollutants model after adjusting the confounders. No significant associations between other air pollutants and AFC were observed. Our finding suggests that long-term exposure to air pollutant SO2 is associated with lower AFC, raising our concern that atmospheric SO2 exposure may have potential adverse impact on women ovarian reserve. Graphical abstract: Image 1 Highlights: Ambient air pollution in Shanxi is at the lowest ranked in China. Increased SO2 level exposure during the development process of antral follicle was significantly associated with lower AFC. The association was particularly significant during the early development transition from primary to preantral stage. Women aged of ≥30 years old may be more susceptible to SO2 exposure. Long-term exposure to soot source pollution may have potential adverse impact on ovarian reserve. Abstract : Long-term exposure to atmospheric pollutant SO2 is significantly associated with decreased antral follicle count, indicating its potentially adverse impact on women ovarian reserve.